The Effect of The ADDIE Model In Productive Thinking Aming Fifth Grade Primary School Students Science (Journal of the College of Basic Education, 2024)
The research aims to identify the impact of the A.D.D.I.E model on productive thinking among fifth-grade primary school students in science. The two researchers chose the experimental method, as behavioral objectives were formulated for the topics to be studied. There were (186) behavioral objectives according to Bloom’s classification, and (40) daily plans were prepared to teach both. The two groups were presented and a model of it was presented to a group of arbitrators to determine the validity and suitability of the plans for the level of fifth-grade primary school students. To achieve the goal of the research, a productive thinking test was prepared, which consisted of (24) test items. The apparent validity was extracted from it by presenting the test to a group of arbitrators in Education and its teaching methods, and to analyze and know the coefficient of difficulty and power of discrimination of the test item, the two researchers used the appropriate statistical methods for the research, and after the completion of the application, the two researchers conducted a post-test for the students of the two groups of the research sample, as the results showed the superiority of the students who studied according to the A.D.D.I.E model over the students of the control group who studied according to the usual method. Based on the results reached by the two researchers, they presented a number of conclusions, recommendations, and proposals that were mentioned in the fourth chapter, and in light of the results that the two researchers reached in the fourth chapter, it can be concluded that teaching with the (A.D.D.I.E) model led to raising productive thinking among fifth-grade students in science, The two researchers recommend enriching science books with activities that help students understand and acquire knowledge and the dimensions of productive thinking, including critical thinking and creative thinking in the academic stages in general and the primary stage in particular. In continuation of this research, the researchers suggest conducting research on the impact of the (A.D.D.I.E) model on achievement and productive thinking among student Intermediate stage in physics